2013
DOI: 10.9735/0975-5276.5.1.357-362
|View full text |Cite
|
Sign up to set email alerts
|

GENES DIFFERENTIALLY EXPRESSED BY Mycobacterium tuberculosis AFTER EXPOSURE TO RUTHENIUM PHOSPHINIC COMPOUND AND ISONIAZID

Abstract: Background- The evaluation of the effects of new compounds and nonconventional anti-tuberculous drugs have grown and become increasingly more popular in recent years. Studies have shown anti-tuberculous activity for Ruthenium complexes, including organometallic compounds containing phosphine ligands such as picolinic acid generating great expectations and hopes.Methods- The Representational Difference Analysis (RDA) was applied in order to gain insight about differences in expression of Mycobacterium tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The structural changes in the ligands and in the complexes probably affect the interaction of the complexes with bacterial membrane. In our previous work with some ruthenium complexes it was suggested that the mechanism of their action against M. tuberculosis occurs in the cell wall biosynthesis [33]. This could be also a suggestion for the mechanism of the biological activity of the platinum complexes here studied, where the interaction of them with the mycobacterium membrane is modulated by the nature of the ligands present in the compounds.…”
Section: Anti-m Tuberculosis Activitysupporting
confidence: 55%
“…The structural changes in the ligands and in the complexes probably affect the interaction of the complexes with bacterial membrane. In our previous work with some ruthenium complexes it was suggested that the mechanism of their action against M. tuberculosis occurs in the cell wall biosynthesis [33]. This could be also a suggestion for the mechanism of the biological activity of the platinum complexes here studied, where the interaction of them with the mycobacterium membrane is modulated by the nature of the ligands present in the compounds.…”
Section: Anti-m Tuberculosis Activitysupporting
confidence: 55%
“…Representational difference analysis is a powerful and sensitive tool for the identification of differentially expressed genes in two different cDNA populations and it allows for detection of changes in mRNA expression by selective enrichment without any prior knowledge of the gene in question (Leite et al 2013 ). Moreover, cDNA-RDA is capable of detecting both relative (greater than three- to five-fold) and absolute differences in expression (Hubank and Shatz 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature on this subject has been quite variable (40)(41)(42). A long exposure time and different concentrations may be related to toxic and side effects and may not represent the primary target of the antimicrobial (23). In the present study, we used 60 min of exposure to 0.5ϫ MIC (meropenem, ciprofloxacin, and the MCC), which represents the beginning of the reduction of viable cells, and antimicrobial concentrations with better synergistic action, assessed by time-kill assays.…”
Section: Discussionmentioning
confidence: 99%